Onconeura, a new Neotropical orthoclad genus (Chironomidae, Orthocladiinae) - Andersen, Trond; Sæther, Ole A. (Zootaxa, 2005)
Diagnoses of all stages of the new genus Onconeura are given. The genus includes O. undecimata new species, from Chile, described as male, female, and pupa, and O. semifimbriata (Sæther) new combination from the Caribbean and Mexico. The genus belongs to the Corynoneura group of genera and appears to form the sister group of Corynoneura Winnertz, Tempisquitoneura Epler, Thienemanniella Kieffer, and perhaps Notocladius Harrison combined. The following combination of characters will separate the genus from the other members of the group: bare eyes; tergites without raised, median area of setae; all trochanters with dorsal keel; hind tibial apex not broadened; male transverse sternapodeme well developed with strong oral projections; female gonocoxite IX well developed but adpressed, with a few setae; coxosternapodeme with a few spine-like anterior projections; and apodeme lobe and labia large. The pupa differs by having 4–7 rows of pearls on the wing sheath, one weak non-taeniate macroseta, and tergal conjunctives with posterior rows of up to 10 strong recurved spines (hooklets). The larva differs from that of Corynoneura and Thienemanniella by having the antenna shorter than half the length of the head, but about one third the length, as opposed to one fourth in Tempisquitoneura.